Penerapan Pembelajaran Berbasisi CAL (Computer Assisted Learning) pada Mata Pelajaran PAI di SMP Negeri 2 Payakumbuh - Mustafa Tito, Dendi; Afrinaldi, Afrinaldi; Charles, Charles; Junaidi, Junaidi (Lembaga Yasin AlSys, 2024)
This research is motivated by the implementation of a CAL (Computer Assisted Learning) based model that is not appropriate or optimal implemented by Islamic Religious Education teachers. This study aims to describe the application of CAL-Based Learning (Computer Assisted Learning) carried out by Islamic Religious Education teachers in Islamic Religious Education class VIII at SMP Negeri 2 Payakumbuh and to find out the obstacles faced by Islamic Religious Education teachers in the implementation of CAL-Based Learning (Computer Assisted Learning) in grade VIII PAI subjects at SMP Negeri 2 Payakumbuh. The results of the research findings conducted by the author show that: The application of CAL-Based Learning (Computer Assisted Learning) in PAI learning is not fully in accordance with the theory and has shortcomings. There are four elements that are studied in this study, namely: Planning, Implementation, Learning Media used, and supporting and inhibiting factors in the Implementation of CAL-Based Learning (Computer Assisted Learning). Obstacles faced by teachers in implementing CAL (Computer Assisted Learning) in Islamic religious education learning include: lack of student learning motivation, lack of student learning activity, lack of student discipline and relatively short allocation of learning time and hours.